A Rapid and Convenient Synthesis of a-Diketones - Chen, Shao-Rui; Ma, Ji-Hai; Zhou, Xue-Qin; Liu, Dong-Zhi (Asian Journal of Chemistry, 2010)
A novel and simple synthetic method for the preparation of series of a-diketones is reported. a-Ditrimethylsiloxyenes were obtained from the readily available materials diacids or diesters through acyloin condensation, which was oxidized to a-diketones using bromine as the oxidation reagent in presence of water. The structures of a-diketones were confirmed by IR, MS, 1H NMR.